Adaptasi permainan tradisional di era digital melalui gamifikasi dan teknologi interaktif - AMALIYA, NADHIFAH (Maliki Interdisciplinary Journal, 2026)
The development of digital technology has changed the way people play, especially children and teenagers who now prefer gadget-based games to traditional games. This situation has made traditional games increasingly rare and could become extinct if there is no ongoing effort to preserve them. Yet, traditional games have cultural, social, and educational values ​​that are crucial in shaping a person's character, such as cooperation, sportsmanship, discipline, and social communication skills. This study aims to examine how traditional games can evolve with current technological advances while maintaining their inherent cultural values. The research method used was a literature review, examining various national and international scientific journals published between 2022 and 2026, covering topics related to the digitalization of traditional games. The research shows that traditional games can be adapted through gamification, creating digital applications, incorporating augmented reality (AR) and virtual reality (VR) technology, and utilizing traditional games as a learning tool using technology. In addition to increasing the interest of the younger generation, digitalization also helps preserve culture in a more creative and engaging way. Therefore, a balance is needed between the use of innovative technology and maintaining cultural values ​​so that traditional games remain relevant to the present, interesting, and can continue amidst the development of the digital world.